The influence of islamic banking digital service quality on intention to continue using islamic banking: a case of Indonesia - Rahma, Nadia; Sofyani, Hafiez (Journal of Accounting and Investment, 2024)
Research aims: Technological advances impact every aspect of daily life, including in Islamic banking. To keep its customers, the Islamic banking industry continues improving the quality of its digital services. Using the DBSQual model, this research aims to examine the quality of Islamic banking digital services, which encompasses seven dimensions: application architecture, application efficiency, responsiveness, user-friendliness, security, reliability, and personalization, towards the intention to continue using Islamic banking.Design/Methodology/Approach: The population of this research was Islamic bank customers in Indonesia. The sample was then selected based on the criteria of Islamic bank customers using mobile banking services. Data collection was carried out by distributing questionnaires developed from previous research. To validate the questionnaire, consultations were conducted with four survey accounting experts. Also, a pilot study was performed. Hypothesis testing was then done using the Structural Equation Modelling technique based on Partial Least Square (PLS-SEM).Research findings: The results demonstrated that three dimensions of digital service quality significantly influenced the intention to continue using Islamic banks, namely application efficiency, security, and reliability. Meanwhile, the dimensions of application architecture and responsiveness had no effect.Theoretical contribution/Originality: This study covers the gap related to empirical studies that examine the role of digital service quality development on intentions to continue using Islamic banking services.